2023
DOI: 10.1038/s41598-023-34281-x
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of composition, antioxidant, antimicrobial and cytotoxic characteristics from Juniperus sabina and Ferula communis extracts

Abstract: Plants have been one the most valuable sources of biologically active compounds. This study investigates the chemical composition, as well as the antioxidant, antimicrobial, and cytotoxic activities of methanolic and ethanolic extracts from Juniperus sabina and Ferula communis leaves, grown in Cyprus. Total phenolic and flavonoids content of methanol and ethanol extracts were quantified. Chemical constituents of the leaf extracts were analysed using gas chromatography/mass spectrometry (GC/MS). Mome inositol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Figure 3 showed that 11 compounds had higher content in Group I and Group II, mainly in the leaves and branches of adult J. sabina . The leaves and branches of J. sabina were the main medicinal tissues in traditional ethnopharmacological applications, which also showed consistency with our clustering results ( Kavaz and Faraj, 2023 ). Significantly, the compounds detected in this study were low in young J. sabina , so age was probably a key factor in the quality of the medicinal tissues of J. sabina ( Ghasemzadeh et al., 2014 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 3 showed that 11 compounds had higher content in Group I and Group II, mainly in the leaves and branches of adult J. sabina . The leaves and branches of J. sabina were the main medicinal tissues in traditional ethnopharmacological applications, which also showed consistency with our clustering results ( Kavaz and Faraj, 2023 ). Significantly, the compounds detected in this study were low in young J. sabina , so age was probably a key factor in the quality of the medicinal tissues of J. sabina ( Ghasemzadeh et al., 2014 ).…”
Section: Resultssupporting
confidence: 89%
“…Juniperus L, represented by 70 species in the world and 23 species in China, belongs to the Cupressaceae family ( Esteban et al., 2023 ; Kavaz and Faraj, 2023 ; Lim et al., 2023 ). The wood, bark and leaves of the juniper genus are rich sources of natural products that can be used as fragrances in alcoholic beverages and cosmetics, with high commercial application value ( Rangel et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F. communis is the second Apiaceae plant in the shortlist of most active native plants. The inhibitory effect of alcoholic and organic extracts derived from F. communis has been determined, but MIC values tested were significantly higher (2000-12,000 µg mL −1 ) for other strains of B. cereus, E. coli, and S. aureus [36]. T. aegyptiacum also belongs to the Apiaceae family and is distributed to the Cyprus and Middle-East regions.…”
Section: Inhibitory Effects Of Native Plants On Gram-positive and -Ne...mentioning
confidence: 99%
“…Ferula species have a long history of extract application in various medical and therapeutic contexts due to their well-documented significant biological activities. These extracts have been utilized in both human and veterinary practice to address a wide range of ailments, including headaches, digestive disorders, rheumatism, arthritis, and tumoral activity [2][3][4][5][6][7]. The biological activities of plant extracts from areal parts and roots were investigated in in vitro experiments involving several fungi, demonstrating fungitoxic effects on colony growth [8].…”
Section: Introductionmentioning
confidence: 99%